COMMUNITY SERVICE PROGRAM (PKM): OPTIMIZATION OF 3R-BASED (REDUCE, REUSE, RECYCLE) WASTE MANAGEMENT AT THE MAPOLI WASTE BANK, KUPANG CITY - Dwi Prasetyo; Alfred OM Dima; Refli; Novita Mariana Tuan; Saritha Kittie Uda (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
The waste problem caused by low public awareness and limited waste management systems remains a crucial issue that leads to environmental degradation. This community service program was initiated as a solution to address the accumulation of unmanaged waste through the implementation of the 3R (Reduce, Reuse, Recycle) concept. Its objectives are to build community self-reliance in waste management, improve environmental quality, and empower local economic potential. Through outreach activities and intensive training, the program was implemented in Kuta Bangun Village. The results indicate the successful implementation of the program, marked by increased understanding and awareness among residents in applying proper waste management practices. In addition to raising awareness, this initiative also succeeded in establishing an independent waste-bank management group as a concrete step toward sustainability. The waste bank not only functions as a center for collecting and sorting waste but also serves as a driving force for the circular economy by converting recyclable inorganic waste into an additional source of income for residents. This success indicates that education- based interventions and community empowerment are effective in transforming behavior and creating a socially and economically sustainable waste management system at the village level.